2021
DOI: 10.3126/jthe.v11i0.38237
|View full text |Cite
|
Sign up to set email alerts
|

Ecotourism in Ghoda Ghodi Wetland Sukhad, Kailali, Nepal

Abstract: Tourism is the act of spending time away from home. Nepal has remained an exotic tourist location for several decades, and wetlands are among the major areas of tourism in Nepal. Located in the far-western Tarai of Nepal, Ghoda Ghodi Lake is among the major wetlands in terms of both biodiversity and tourism. This study has assessed the ecotourism status in Ghoda Ghodi Lake of Nepal and to understand the current condition and possible inferences. A total of 40 households were surveyed, and 80 visitors were inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The study found the opposite opinions regarding culture and traditional preservation. Our study found that cultural value is degraded upon international tourists' arrival (Khadka et al, 2021), which may be due to western cultural influence (Tosun, 2002) and the local workforce's inadequacy to perform their cultural shows in the community. However, the majority (64%) of the visitor perceived the culture and traditions would be preserved by the local household for the sake of economic benefits (Besculides et al, 2002;Meleddu, 2014).…”
Section: Discussionmentioning
confidence: 81%
“…The study found the opposite opinions regarding culture and traditional preservation. Our study found that cultural value is degraded upon international tourists' arrival (Khadka et al, 2021), which may be due to western cultural influence (Tosun, 2002) and the local workforce's inadequacy to perform their cultural shows in the community. However, the majority (64%) of the visitor perceived the culture and traditions would be preserved by the local household for the sake of economic benefits (Besculides et al, 2002;Meleddu, 2014).…”
Section: Discussionmentioning
confidence: 81%